Secretome analysis: reading cellular sign language to understand intercellular communication - Wu, Wei; Krijgsveld, Jeroen (Molecular & cellular proteomics, 2024)
A significant portion of mammalian proteomes is secreted to the extracellular space to fulfill crucial roles in cell-to-cell communication. To best recapitulate the intricate and multi-faceted crosstalk between cells in a live organism, there is an ever-increasing need for methods to study protein secretion in model systems that include multiple cell types. In addition, posttranslational modifications further expand the complexity and versatility of cellular communication. This review aims to summarize recent strategies and model systems that employ cellular coculture, chemical biology tools, protein enrichment, and proteomic methods to characterize the composition and function of cellular secretomes. This is all geared towards gaining better understanding of organismal biology in vivo mediated by secretory signaling.
Online verfügbar: 10. Dezember 2023, Artikelversion: 3. Januar 2024
Gesehen am 06.06.2025